Overactive bladder-18 years - Part I - Truzzi, Jose Carlos [UNIFESP] (2016)
Overactive bladder syndrome is one of the lower urinary tract dysfunctions with the highest number of scientific publications over the past two decades. This shows the growing interest in better understanding this syndrome, which gathers symptoms of urinary urgency and increased daytime and nighttime voiding frequency, with or without urinary incontinence and results in a negative impact on the quality of life of approximately one out of six individuals - including both genders and almost all age groups. The possibility of establishing the diagnosis just from clinical data made patients' access to specialized care easier. Physiotherapy resources have been incorporated into the urological daily practice. A number of more selective antimuscarinic drugs with consequent lower adverse event rates were released. Recently, a new class of oral drugs, beta-adrenergic agonists has become part of the armamentarium for Overactive Bladder. Botulinum toxin injections in the bladder and sacral neuromodulation are routine modalities of treatment for refractory cases. During the 1st Latin-American Consultation on Overactive Bladder, a comprehensive review of the literature related to the evolution of the concept, epidemiology, diagnosis, and management was conducted. This text corresponds to the first part of the review Overactive Bladder 18-years.